Shipping noise tolerance in invertebrates: A case study of the shore crab Hemigrapsus oregonensis - Abigail Birch; Kieran D. Cox; Kelsie A. Murchy; Sandra Emry; Christopher D. G. Harley (PLoS ONE, 2025)
Recent decades have seen significant alterations to ocean soundscapes. These changes are primarily driven by human-generated sources (i.e., anthropogenic noise), which is now recognized as a marine pollutant of emerging concern. In contrast to research on marine mammals and fish, studies on the effects of noise on marine invertebrates are limited, and while behavioural changes have been observed in some invertebrate taxa, few investigations have considered whether marine invertebrates can develop a tolerance to this pollutant. We examined the behavioral impacts of shipping noise on the shore crab Hemigrapsus oregonensis and whether they can develop tolerance to noise. Cohorts collected from sites with low and high noise levels were exposed to playbacks of ship noise in the laboratory. We measured initial responses to a simulated predator attack, time taken to seek shelter following the attack, and disruption during feeding. Our results indicated that ship noise significantly impacts shore crabs’ initial response after a simulated predator attack, with a 66% likelihood of movement in noise-exposed individuals compared to 32% in the controls. However, ship noise did not significantly impact whether the crabs retreated to shelter after a predator attack, nor did it disrupt feeding. The interaction between treatment and site type was not significant for any of the behavioral metrics, indicating no evidence of tolerance related to prior noise exposure. Finally, we assessed broader relationships between sound and marine arthropods’ behavior by combining our results with 71 data points extracted from 17 published studies. A meta-analysis of these data indicated that sound can have a positive, negative, or null effect on marine arthropods. Our results highlight the importance of considering marine invertebrates when evaluating the ecological impacts of anthropogenic noise, and suggest that more work is required to identify the contexts in which this emerging pollutant is particularly detrimental.